Resource allocation in Education and Socio-economic Education Development in the Small Industry in India - Uma Shankar Yadav; Mano Ashish tripathi; Ravindra Tripathi (East Asian Journal of Multidisciplinary Research, 2022)
Economy of India can't accomplish the objective of sustainable economic development and education about small industries to the resource like human resources, until or unless it can put a generous sum in human resources. Education is a fundamental factor of development. It does not just improve the personal satisfaction of an individual yet in addition improves the social advantage of the public. The motivation behind this examination to discover how public expenditures on education can improve the economic and social state of the society in India. Regardless, the issue that whether further developed level of education coming about on the grounds that more education spending can advance economic growth is yet sketchy. A few economic and social analysts and researchers have maintained the two-sided connectivity between these two factors, yet some are recommending that economic growth essentially animates government to spend more on education, not the substitute way. The research question of this paper is "do education and expenditures on education get economic and social ith eduction of small industry advancement"? Considering this research issue, the current paper utilizes Granger Causality methods to conclude the causal connection between government's education spending and socio-economic development in India for the period 1972-2021. Results uncovered that there is no short run causality between government expenditure on education and socio-economic growth, yet economic growth influences public spending on education. This provides guidelines to the new education policy(NEP) makers that they should priorities their attention towards allocation of development and non-development expenditures of government’s budget to enhance the quality of education and welfare of individuals in the society. Special focus should be given on the compulsory primary education which is already a part of sustainable development goals.